INVESTIGATING THE IMPACT OF PROFESSIONAL EXPERIENCE AND EDUCATIONAL BACKGROUNDS ON NURSING CARE QUALITY - Ayidah Ghazai Mazyad Aljameeli, Masirah Hamed Ghushum Aljameeli, Nouf Mohammed Bateh Aljameeli, Seham Hamoud Alhamidi Aljameeli, Shahah Turki Lufan Aldhafeeri, Wasayf Marshad Saad Aljameeli (Chelonian Research Foundation, 2022)
Nursing care quality is a critical aspect of healthcare delivery, directly impacting patient outcomes and overall well-being. This study aimed to investigate the influence of professional experience and educational backgrounds on nursing care quality. A mixed-methods approach was employed, combining quantitative data from patient surveys and clinical indicators with qualitative insights from focus group discussions and semi-structured interviews. The quantitative component involved a cross-sectional analysis of patient satisfaction scores, medication error rates, and nurse-sensitive patient outcomes across various healthcare facilities. The qualitative component explored nurses' perspectives, challenges, and strategies related to providing high-quality care. Participants included 500 nurses with diverse educational backgrounds and levels of professional experience from multiple healthcare settings. The findings revealed a significant positive correlation between years of professional experience and patient satisfaction scores, as well as lower medication error rates. Additionally, nurses with higher educational qualifications, such as bachelor's or master's degrees, exhibited better performance in nurse-sensitive patient outcomes. Qualitative data highlighted the importance of continuous professional development, interdisciplinary collaboration, and supportive work environments in enhancing nursing care quality. This study contributes to a comprehensive understanding of the factors influencing nursing care quality and provides valuable insights for healthcare organizations, policymakers, and educational institutions to develop strategies that optimize patient outcomes and promote excellence in nursing practice.